2019
DOI: 10.1039/c9gc02499a
|View full text |Cite
|
Sign up to set email alerts
|

An effective hybrid strategy for converting rice straw to furoic acid by tandem catalysisviaSn-sepiolite combined with recombinantE. coliwhole cells harboring horse liver alcohol dehydrogenase

Abstract: The upgrading of biomass-derived furfural into high-value bio-based chemicals has attracted interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
0
34
0
1
Order By: Relevance
“…Sulfonated vermiculite (4.0 wt %) catalyzed the conversion of reeds into FAL (55.0 mM) in a yield of 38% at 170 °C within 20 min . Sulfonated sepiolite (3.0 wt %) was used to transform rice straw into FAL in 42% yield in 20 min at 170 °C . Compared to these work, ,,,, high FAL at a concentration was formed using low dose of the SS-based catalyst in our work.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Sulfonated vermiculite (4.0 wt %) catalyzed the conversion of reeds into FAL (55.0 mM) in a yield of 38% at 170 °C within 20 min . Sulfonated sepiolite (3.0 wt %) was used to transform rice straw into FAL in 42% yield in 20 min at 170 °C . Compared to these work, ,,,, high FAL at a concentration was formed using low dose of the SS-based catalyst in our work.…”
Section: Resultsmentioning
confidence: 77%
“…The CC components were analyzed according to the reported method. 46 XPS, XRD, NH 3 -TPD, BET, SEM, and FT-IR analyses were performed as reported in ref 17.The content of FAL or FLA in the DES−water system was quantified using a HPLC Model 2695 (Waters Corporation, Milford, MA). 34 The relevant formula for calculations are given as follows FAL yield(%) FAL produced(g) 0.88 CC(g) 0.31…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The content of M5HF2C of each mutant in the Fries 3 medium was consistent with the expression of Clpks18 gene. In the Fries 3 medium, the Clpks18 deleted mutants’ acetaldehyde dehydrogenase low expression (unpublished data), which maybe related to the M5HF2C biosynthesis ( Peng et al, 2019 ). However, the difference between the content of M5HF2C toxin in maize leaves infected by WT and other mutants was not significant ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 98%
“…Besides the chemical synthesis of FCA, Peng et al reported an efficient one-pot chemo-enzymatic approach for the conversion of rice straw to form FCA through a tandem catalyst with Sn-sepiolite and whole-cell harboring horse liver alcohol dehydrogenase (HLADH) under mild reaction conditions. 60 The Sn-sepiolite could effectively convert rice straw to furfural in 42.2% yield at 170 °C for 20 min. Subsequently, the resulting furfural could be completely oxidized to FCA with E. coli TS whole-cells within 96 h at room temperature.…”
Section: Catalytic Conversion Of Furfural Into Value-added Chemicalsmentioning
confidence: 96%